Metaliterary Layers in Finnish Literature - Turunen, Risto; Hägg, Samuli; Sevänen, Erkki (Studia Fennica Litteraria, 2009)
In international research, metafictionality and other metaliterary features have typically been regarded as phenomena related to postmodernist fiction, in particular - Metaliterary Layers in Finnish Literature, however, discusses the metalayers of Finnish literature from the early 20th century to the present. By analyzing different genres of Finnish literature in varying historical contexts Metaliterary Layers in Finnish Literature provides an abundance of new information on Finnish literature and its metaliterary phenomena for everyone interested. In the articles of this book, the metalayers of literature are discussed in experimental prose and poetry as well as in popular fiction and children's literature.